Epigenome-wide association study and network analysis for IgA Nephropathy from CD19+ B-cell in Chinese Population. Issue 12 (2nd December 2021) - Lin, Yifei; Yin, Peiran; Zhu, Zhaozhong; Peng, Yuan; Li, Ming; Li, Jun; Liang, Liming; Yu, Xueqing
ABSTRACT: IgA nephropathy (IgAN) is the most common primary glomerular disease in China and worldwide. The proliferation of B cells is known to be associated with both risk and prognosis of IgAN, but the epigenetic mechanism underlying this association is unknown. In this study we carried out the first Epigenome-wide Association Study (EWAS) by using the latest Infinium Methylation EPIC BeadChip on 184 B cell-specific samples (92 case/control pairs) for Chinese IgAN population. After rigorous data normalization and residual batch effect correction, linear mixed effect model was used to detect methylation CpG sites associated with IgAN adjusting for age, gender and smoking. False discovery rate ( FDR ) less than 10% was used to account for multiple testing. Weighted gene co-methylation networks were generated to identify gene modules highly correlated with IgAN. A permutation test was performed to account for the potential effect of overfitting. After adjusting clinical covariates and potential technical batch effects, three CpGs corresponding to PCDH17, TERT, WDR82 genes and three in the intergenic regions passed the genome-wide significant threshold. Methylation network analysis identified an additional IgAN associated gene module, containing 72 significant CpGs including GALNT6, IQSEC1, CDC16 and SYS1, involved in the pathway related to tubular atrophy/interstitial fibrosis of IgAN. These results suggested important DNA methylation and gene targets in CD19 +  B cells for the pathogenesis of IgAN.